Economic Losses of Unused Medicines Among Households in Grobogan Regency - Sulistyaningrum, Indriyati Hadi; Santoso, Arifin; Fathnin, Fildza Huwaina; Nugrahaini, Atmarulin Dewi; Arfianto, Erki; Maulidina, Herlisa (Pharmacon: Jurnal Farmasi Indonesia, 2023)
All medicines that are stored and no longer used will be returned to pharmacies, health professionals, thrown away at medicine collection points or through household waste which can be considered as medicine waste. Medical waste from unused or expired medicines is thought to have financial consequences. This research is a descriptive quantitative observational study using a cross sectional study method. Sampling was carried out using the Snowball Sampling method. The sample obtained consisted of 271 household respondents from 19 sub-districts in Grobogan Regency. Data collection was carried out using a questionnaire indirectly via Google Form using descriptive analysis. The results of the research were that the largest number of drugs not used and stored based on therapeutic class was the analgesic group, namely Rp. 610,249 (37%). The total estimated value of unused drugs from 13 therapeutic classes is IDR. 2,609,388 with an average per household of IDR 9,629. The conclusion of the research is that the value of unused medicine can illustrate that the amount of wasted costs to households is IDR 9,629.